2018
DOI: 10.1159/000490473
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Blood Purification Ameliorates Multiple Organ Failure Through Inhibiting the Activation of the P38 MAPK Signaling Pathway in a Rat Model

Abstract: Background/Aims: Multiple organ failure (MOF) is a primary threat to the survival of patients with systemic inflammation. Blood purification is employed in the treatment of MOF, as an artificial kidney or artificial liver. This study focuses on the effects of continuous blood purification (CBP) on ameliorating MOF through regulating the p38 mitogen-activated protein kinase (MAPK) signaling pathway in a rat model. Methods: A rat model of MOF was successfully established by endotoxin injection after hemorrhagic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Various stimuli, such as pro‐inflammatory factors, cytokines, and cellular stress, can phosphorylate p38MAPK via the protein kinase cascade. Phosphorylated p38MAPK will get access to the nucleus, regulating the inflammatory response and cellular immune response . In our study, we found out that the protein level of p‐p38MAPK was significantly higher in the blood sample of patients with MODS and the p‐p38MAPK induced by serum from patients with MODS was also significantly increased compared to control group ( P < 0.05).…”
Section: Discussionmentioning
confidence: 52%
“…Various stimuli, such as pro‐inflammatory factors, cytokines, and cellular stress, can phosphorylate p38MAPK via the protein kinase cascade. Phosphorylated p38MAPK will get access to the nucleus, regulating the inflammatory response and cellular immune response . In our study, we found out that the protein level of p‐p38MAPK was significantly higher in the blood sample of patients with MODS and the p‐p38MAPK induced by serum from patients with MODS was also significantly increased compared to control group ( P < 0.05).…”
Section: Discussionmentioning
confidence: 52%
“…A study shows that inhibition of p38 mitogen-activated protein kinase largely improves resulting vascular dysfunction [ 5 ]. Other studies enhanced that continuous BP could potentially downregulate the p38 MAPK signaling pathway, suppress inducible nitric oxide synthase expression, reduce the serum levels of nitric oxide and TNF-α, and thus improve symptoms of multiple organ failure [ 36 , 37 ].…”
Section: Why Does Extracorporeal Bp Make Sense For Severe Burn Injury?mentioning
confidence: 99%